PENGARUH PENGGUNAAN BERBAGAI MACAM VARIETAS MANGGA TERHADAP KUALITAS NATA DE MANGO - Frengki Saputra; Rahma Hidaiyanti (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
Mango (Mangifera indical L) during the harvest season arrives abundant in number, so the prospect of declining sales prices, one mango fruit processing alternative is to process it into a type of nata de mango products. Nata is a food gel (gelatin) with a slightly chewy texture, white and transparent (resembling fro). The purpose of this study on the effect of the use of various varieties of mangoes on the quality of nata de mango. the analysis in this study includes the analysis of fiber content, texture and organoleptic (color, taste, texture dam) nata de mango. the results of the analysis of the fiber content of nata de manggo showed that mango types of treatment used in penggolahan nata de manggo fiber content ranges from 1.43% to 2.35%, the results of texture analysis nata de manggo with numbers up to 102 73.00 mm, 67 mm and based on the results of organoleptic test of flavor, color and texture that the type of treatment used mango shows a noticeable difference.Keywords: Mango, Nata, Nata de Mango